Analysis Head Nurses' Leadership Styles to Staff Inpatient Nurses' Job Performance Royal Prima Hospital - Ryeo Ramadhan Chairun; Marlinang Isabela Silalahi; Sri Lestari Nasution (CV. Inara, 2024)
lack of research in knowing the relationship between nurse leadership styles and nurse performance. Data collection by interviews, questionnaires and observations on inpatient nurses at Rotal Prima Hospital Medan. This study tries to examine the influence of the Job Performance Nurse dimension which is influenced by the dimensions of the Transactional Leadership Style and the Transformational Leadership Style of Head Nurses. This research is associative, with a quantitative method approach, using a descriptive correlational research design. The research was validated using SPSS-26 with data analysis techniques using multiple linear regression analysis. The results showed that the Transactional Leadership Style and Transformational Leadership Style had a positive and significant effect on Nurse Job Performance. The results of this study, we found that nurse leaders must have a good transformational leadership style so that leaders can help and encourage their subordinates in providing training and achieving their work goals properly. Nurse leaders are more likely to adopt a transformational leadership style. The results of this study also show that transactional leadership can affect nurse performance, although it is even better if the head nurse performs transformational leadership.